Hyperuricemia and Hypertension — A Causal Relationship Ignored For All Too Long - Pater, Cornel (Current Hypertension Reviews, 2011)
Soluble uric acid (UA) has traditionally been viewed by most scientific authorities as a biologically inert substance, possibly having anti-inflammatory properties as an antioxidant. Compelling evidence from a multitude of experimental and clinical studies carried out worldwide by different groups during the past two decades indicate that an elevated serum uric acid in humans is associated with hypertension, cardiovascular and kidney disease, diabetes and obesity as well as systemic inflammation, increased CRP and endothelial dysfunction. Hyperuricemia induces hypertension and renal injury via a crystal-independent mechanism, involving renal vasoconstriction mediated by endothelial dysfunction and activation of renin-angiotensin system. The epidemic increase in prevalence of hypertension, obesity, metabolic syndrome and diabetes in all societies suggest that these pathologic entities may be pathogenetically related and basically linked to environmental and dietary changes that have occurred and affected the human kind over the past century. Whereas classical risk factors like excessive caloric intake, physical inactivity and smoking will maintain their importance as major determinants in the occurrence of disease, a reappraisal of an old hypothesis - fructose induced hyperuricemia is leading to development of cardio-renal disease - may open the way toward new approaches to prevention and management of hypertension, and of various hypertension-related disease entities.
Keywords: NADPH